Pengaruh Keandalan Akrual, Tingkat Utang Dan Ukuran Perusahaan Terhadap Persistensi Laba - Yulira Gusnita; Salma Taqwa (Universitas Negeri Padang, 2019)
This study aims to examine and find empirical evidence regarding the effect of accrual reliability, leverage and firm size on earnings persistence. The population in this study were all financial sector companies listed on the Indonesia Stock Exchange in 2014-2017. By using a purposive sampling technique obtained as many as 40 financial sector companies that will be used as research samples. The data analysis method used is multiple linear regression analysis. The results showed that accrual reliability, debt level and company size simultaneously had a significant effect on earnings persistence. But partially only company size has a significant positive effect on earnings persistence, while accrual reliability does not have a significant positive effect on earnings persistence and debt level has a significantly negative effect on earnings persistence in financial sector companies listed on the Indonesia Stock Exchange in 2014-2017.